KNOWLEDGE AND PRACTICE OF USING ANTIBIOTIC FOR CHILDREN UNDER 5 YEARS OLD OF MOTHERS IN LIEM CAN COMMUNE, THANH LIEM DISTRICT, HA NAM PROVINCE IN 2024 (Vietnam Journal of Community Medicine, 2026)
1) Objectives: To describe the knowledge and practice of using antibiotic for children under 5 years old of the mothers in Liem Can commune, Thanh Liem district, Ha Nam province in 2024.2) Research method: The study applied “cross-sectional descriptive design”; the data was collected by interviewing 96 mothers who are having children under 5 years old. 3) Results: The percentage of mothers who have good knowledge of using antibiotic is relatively low (52,1%). Only 52,1% of mothers said that "antibiotic need to be used in the right dose";  46,9% of mothers answered that antibiotic need to be used during the exact number of days prescribed. The percentage of mothers comply with doctor’s prescriptions when using antibiotic is quite low (59%). About two-thirds of mothers check the expiry date of the drug before using (66,7%). The rate of mothers taking their children to the doctor for re-examination if the children’s disease symptoms do not decline after 3 days of using drug is relatively low (53,8%); 25.6% of mothers automatically changed antibiotics for their children when they saw that their children did not get better after 3 days.4) Conclusion: In general, mothers' knowledge about using antibiotic is limited (only 52,1% of mothers have good knowledge about antibiotic use). Practicing of compliance with prescription when using antibiotic of the mothers is quite bad (only 59% of mothers let their children use antibiotic according to doctors’ prescription). About half of the mothers sent their children to the doctor again after 3 days of taking the medicine, and up to 25.6% of mothers automatically change antibiotics for their children.
Keywords: Knowledge; Practice; Using antibiotic; Mothers